2004
DOI: 10.1016/j.amjhyper.2004.03.674
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of sour milk on blood pressure in borderline hypertensive men

Abstract: This trial demonstrated the beneficial effect of sour milk on BP in borderline hypertensive men who were not taking antihypertensive medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 24 publications
6
85
0
4
Order By: Relevance
“…[1][2][3] Other studies suggest that 2-4 weeks is not long enough and that at least 6-12 weeks of intervention are needed to elicit a longerterm LTP-induced effect. [4][5][6][7][8] The latter studies are more in line with our observation, as we did not observe a significant additional 4-week effect. Therefore, we can only speculate that the blood pressure-lowering effect is already present at the first day of consumption and that this effect is repeated on every new day that the LTP-containing product is consumed, with only a very small additional chronic effect after at least 6 weeks of intervention.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…[1][2][3] Other studies suggest that 2-4 weeks is not long enough and that at least 6-12 weeks of intervention are needed to elicit a longerterm LTP-induced effect. [4][5][6][7][8] The latter studies are more in line with our observation, as we did not observe a significant additional 4-week effect. Therefore, we can only speculate that the blood pressure-lowering effect is already present at the first day of consumption and that this effect is repeated on every new day that the LTP-containing product is consumed, with only a very small additional chronic effect after at least 6 weeks of intervention.…”
supporting
confidence: 92%
“…Several placebo-controlled studies show that ingestion of LTP-containing fermented products for several weeks can reduce systolic and diastolic blood pressure (SBP/DBP) in high normal-to-mild hypertensive subjects. [1][2][3][4][5][6][7][8][9] However, limited information about the acute effects of LTPs during the first hours after ingestion is available. Thus, it remains unknown whether intake at frequencies less than daily over weeks would have similar blood pressure-lowering effects.…”
mentioning
confidence: 99%
“…The Dietary Approaches to Stop Hypertension trial demonstrated that a dietary pattern abundant in fruits, vegetables and low-fat dairy products can considerably reduce BP (25) . Data from Study Net change 95% CI Weight (%) Hata (1996) (6) Agerholm-Larsen (2000) (7) Kawase (2000) (8) Inoue (2003) (9) Seppo (2003) (10) Mizushima (2004) (11) Tuomilehto (2004) (12) Aihara (2005) (normotensive) (13) Aihara (2005) (hypertensive) (13) Jauhiainen (2005) (14) Engberink (2008) (15) van der Zander (2008) (16) Jauhiainen (2010) (17) Usinger ( Study Net change 95% CI Weight (%) Hata (1996) (6) Agerholm-Larsen (2000) (7) Inoue (2003) (9) Seppo (2003) (10) Mizushima (2004) (11) Tuomilehto (2004) (12) Aihara (2005) (normotensive) (13) Aihara (2005) (hypertensive) (13) Jauhiainen (2005) (14) Jauhiainen (2010) (17) Usinger (2010 Fig . 3.…”
Section: Discussionmentioning
confidence: 99%
“…15 16 157 (7) 94 (6) 52 (8) 50 16 158 (12) 95 (8) 50 (8) 44 Seppo et al 16 10 148 (13) 94 (6) 49 (6) 30 7 148 (13) 93 (3) 46 (13) 29 Seppo et al 17 22 155 (13) 97 (6) 51 (7) 46 17 152 (13) 96 (6) 48 (7) 53 Mizushima et al 18 23 148 (10) 95 (10) 44 (10) 100 23 145 (13) 92 (10) 48 (9) 100 Toumilehto et al 19 30 153 (10) 98 (7) 51 (10 150 (13) 85 (9) 60 (7) 56 139 150 (13) 86 (9) 60 (7) 55 Van Mierlo et al 26 31 147 (9) 89 (6) 62 (7) 65 38 147 (9) 89 (6) 62 (7) 19 2.5 mg VPP and 2.5 mg IPP peptides 150 ml fermented milk with L. helveticus 10 Aihara et al 20 8.3 mg VPP and 4.7 mg IPP peptides 12 gr dried product from fermented milk with L. Helveticus 4 Jauhiainen et al 21 30 mg VPP and 22.5 mg IPP peptides 300 ml fermented milk with L. helveticus 10 Mizuno et al 22 3.6 mg VPP and IPP peptides Two tablets of hydrolyzed casein 6 Sano et al 23 1.47 mg VPP and...…”
Section: Discussionmentioning
confidence: 99%
“…Number, age-and sex-ratio of participants, duration of intervention, baseline systolic (SBP) and DBP, change at end of intervention and daily amount of active component or placebo product were obtained from each trail (Tables 1 and 2 [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] ). In a trial by Mizuno et al, 22 participants were given different amounts of active product.…”
Section: Data Abstractionmentioning
confidence: 99%